Integrasi Profil Fitokimia Berbasis GC–MS dan Evaluasi Farmakologis In Vivo dalam Menilai Potensi Antidiabetes Ekstrak Etanol Scleria sumatrensis Retz. pada Model Tikus Diabetes Induksi Aloksan. - Douglas Natan Pareta; Friska Mery Montolalu; Aprillia Vincensia Keno; Jabes Wolter Kanter; Joke Luis Tombuku; Christel Nataniel Sambou; Andri Natanel; Rahmat Santoso; Hariyadi Hariyadi; Alter Yantje Runtu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
This study evaluated the antidiabetic activity and phytochemical profile of the ethanolic extract of Scleria sumatrensis Retz. Using an alloxan-induced diabetic rat model. Diabetes was induced by a single intraperitoneal injection of alloxan (150 mg/kg BW) after a 12-hour fasting period, and fasting blood glucose was measured at three standardized time points: GD1 (baseline), GD2 (72 hours post-induction), and GD3 (day 14 post-treatment). GC–MS analysis revealed several major constituents, including ethyl α-D-glucopyranoside, ethyl linoleate, ethyl linolenate, phytol, tocopherol, and β-sitosterol, which are associated with improved insulin sensitivity, modulation of PPAR-γ–related pathways, antioxidant protection of pancreatic β-cells, and reduced intestinal carbohydrate digestion. Rats were assigned to negative control (vehicle), positive control (metformin 45 mg/kg BW), and extract-treated groups (75, 150, and 300 mg/kg BW). Percentage reduction from GD2 to GD3 was analyzed using one-way ANOVA followed by Tukey’s post-hoc test. The extract produced a significant and dose-dependent decrease in fasting glucose (p < 0.001). All extract doses differed significantly from the negative control, and the 300 mg/kg dose demonstrated glucose-lowering efficacy comparable to metformin. These findings indicate that Scleria sumatrensis possesses vigorous antihyperglycemic activity consistent with its lipophilic phytochemical composition. Further studies are required to verify the underlying mechanisms and identify the most active constituents.